Borneo enterprise: infinite candle / Melvin Danes ...[et al.] - Danes, Melvin; Zulkiplie, Armin Zakhrin; Norlaziman, Muhammad Haziq; Mohd Noor Azmi, Nur Aziatul Hajrah; Jebat, Syifa' Nasuha; Saharudin, Syafiqah Amirah (2017)
Borneo Enterprise is located Persiaran Seri Alam, Bandar Seri Alam, 81750 Masai, Johor. Borneo Enterprise is a company which focusses on domestic in human life. Company produces Infinite Candle which has different function compare with the usual candle out there.